2020
DOI: 10.1021/acs.macromol.9b02127
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Rheological Analysis of Polystyrene-Grafted Silica Nanocomposites

Abstract: Two matrix-free polystyrene-grafted silica nanocomposite samples with graft chain lengths of 35 and 112 kg/mol are characterized by calorimetry and rheometry, and results are compared to neat polystyrenes of comparable molecular weights. The glass transition temperature T g of the nanocomposites is found to be approximately 1 to 2 K higher than that of the neat materials, whereas the absolute heat capacity is approximately 4–7% lower in the glassy and liquid states. The step change in heat capacity ΔC p at T g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 128 publications
8
31
1
Order By: Relevance
“…When GNPs or star polymers (which represent the limiting case of GNPs with a very small core) or ordered block copolymer spherical micelles are self-suspended in the melt state (i.e., in solvent-free conditions), they interact in a completely different way in comparison to the case in which they are placed in a polymeric matrix or a molecular solvent. , This is the focus of the current work. In fact, GNPs with high enough grafting density and long-enough grafted chains are well-dispersed and interact primarily via their coronas which can interpenetrate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When GNPs or star polymers (which represent the limiting case of GNPs with a very small core) or ordered block copolymer spherical micelles are self-suspended in the melt state (i.e., in solvent-free conditions), they interact in a completely different way in comparison to the case in which they are placed in a polymeric matrix or a molecular solvent. , This is the focus of the current work. In fact, GNPs with high enough grafting density and long-enough grafted chains are well-dispersed and interact primarily via their coronas which can interpenetrate .…”
Section: Introductionmentioning
confidence: 99%
“…This feature was shown to be accompanied by an increase of the strength of the effective cage (which reflects the topological constraints of neighboring particles), as evidenced by the time evolution of the plateau storage modulus. Another study 20 reported the absence of terminal flow within the experimentally accessible time window. Such behavior was attributed to the coupling between arm interpenetration and particle localization (due to interparticle interactions); however, there was no explicit discussion of structural or jamming dynamics (i.e., the decoupling of polymeric and colloidal modes).…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the final behavior of the NPs is influenced by the chemical composition of the grafted chains, but also by their degree of polymerization (N) and their grafting density, the number of grafted chains per unit of area (σ). Variations in N and σ in systems where the polymer chains are tethered to hard and rigid nanoparticle core, such as silica or gold, influence the dynamics of the grafted polymer chains.And the architecture of the canopy of grafted polymer chains defines the interfacial properties of the NPs, such as particle/particles interaction or NPs/solvent interaction [6][7][8][9][10][11]. However, the behavior of systems where the core is itself soft and deformable like a nanogel has not been addressed, and the dynamics of polymer chains grafted on the surface of soft NPs need to be thoroughly understood to improve the design of such systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…The architecture of the grafted polymer system, defined by the σ and N of the canopy, affects the conformation [13][14][15] and the dynamics of the grafted chains [16]. Both of which, in turns, largely affect the macroscopic behavior of systems based on polymer-functionalized NPs, such as the mechanical properties of nanocomposites [16,17] or the rheology of colloidal suspensions [11,16,18]. In a polymer-grafted NPs system, usually, the polymer chains experience a deceleration of the relaxation in comparison to free chains as a consequence of the stretched chain conformation near the surface of nanoparticles and increased confinement generated by the proximity of adjacent chains [19] at least at the scale of the local segmental motion.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-grafted nanoparticles represent a unique subfield of functional materials with a beneficial combination of properties from inorganic nanoparticles and chemically grafted polymeric chains. Grafting polymers to nanoparticle surfaces influences their thermomechanical properties, chain conformations, dispersity, and assembly behaviors. For example, several theoretical simulations revealed a transition of chain conformation from stretched (close to the particle surface) to relaxed at low grafting density or high degree of polymerization. , Experimental efforts on polymer nanocomposites have also shown that control of chain length and graft density is crucial for property enhancements and dispersion of nanofillers within the polymer matrix. ,, …”
mentioning
confidence: 99%